The Relationship between Vitamin C Adequacy with the Incidence of Anemia among Female Nutrition Students at Universitas Negeri Surabaya - Letsoin, Maria Jessica; Mayasari, Noor Rohmah (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Background: One of the factors that causes the high incidence of anemia is inadequate nutritional intake, such as iron, vitamin C, vitamin A, vitamin B12, riboflavin, and folate. Vitamin C plays a role in the absorption of iron, which is necessary to form hemoglobin. Purpose: This study was aimed to describe and analyze the relationship between vitamin C adequacy and the incidence of anemia among female nutrition students at Surabaya State University. Methods: The study was conducted using an observational, cross-sectional design and a stratified random sampling method. The sample consisted of 247 female nutrition students. Vitamin C adequacy data were collected by a 3x24-hour Food Record and analyzed using the Chi-Square test. Result: The average intake of vitamin C in nutrition students only reached 34.4 mg/day with a percentage of anemia incidence reaching 47.8%. However, the data analysis revealed no statistically significant correlation between vitamin C adequacy and the incidence of anemia among female nutrition students at Universitas Negeri Surabaya (p=0.841). Conclusion: The incidence of anemia in female nutrition students is influenced not only by the adequacy of vitamin C, but also by other factors, such as the intake of other nutrients and the presence of infection.